EFFECT OF CHITOSAN COATINGS ON PRESERVATION OF RED SNAPPER (Lutjanus argentimaculatus Forsskal, 1775 ) DURING LOW TEMPERATURE STORAGE - Pramono, Heru; Wahyuni, Tri; Abidin, Faris; Ardianto, Wahyu; Sumartono, Fareza Ferdyna Nanda (JFMR (Journal of Fisheries and Marine Research), 2018)
The effect of three different concentration of chitosan (0, 1.5 andÂ  2 % w/v) on microbiological (aerobic plate count), chemicals (pH and total volatile basic nitrogen, TVB-N), and sensory properties of red snapper (Lutjanus argentimaculatus Forsskal, 1775) during cold storage (4-7oC) was evaluated periodically. The microbiological quality of red snapper coated with chitosan was lower compared to control, whereas pH and TVB-N were lower when treated with chitosan. The overall score of sensory evaluation of chitosan with concentration of 1% (w/v) was higher compared to remaining treatments. This study indicates that coating of chitosan prior to storage and distribution of red snapper prolong the shelf life of the fish but the microbial quality during storage is depend on initial quality of the fish.Â